Development and implementation of nutrion strategies to improve the application of a food-based dietary guideline for use by créche caregivers in Thulamela Limpopo Province, South Africa - Van der Spuy, Hester Helena (University of Pretoria, 2013)
Dissertation (MConsumer Science)--University of Pretoria, 2010.